Playful strategies and literary creation - Quispe Torres, Leoncio Daniel (2020)
The research entitled "Playful strategies and literary creation" is an approach to solving problems such as how does the application of playful strategies influence the creation of literary texts in university students of the UNSCH of Ayacucho, 2015? The objective is to determine the nature of the influence of the application of playful strategies in the creation of literary texts. The type of research is basic and qualitative. Well, it is about proposing a teaching model. The level corresponds to the descriptive-explanatory. The method that is applied is the inductive-deductive mixture. The main result and conclusion reached is: The application of playful strategies for the creation of literary texts directly, naturally, spontaneously and systematically influences the scriptural conception of literary texts.